Study of micro movements in sewing tasks with industrial sewing machines. (Innovation & Development in Engineering and Applied Science, 2023)
This research is a documentary, quantitative and experimental study, which analyzes the micro movements in the manufacturing tasks with industrial sewing machines through the study of methods for the design of predetermined times for the manufacture of basic T-shirts. For this purpose, the situation of the Xiomac company was studied segregated into three integral phases. Phase 1: determination of the cycles to be studied; Phase 2: information gathering and analysis of the use of different work execution methodologies; Phase 3: labor optimization and layout redesign through personalized training, which finally resulted in the reduction of production time, ergonomic risks and the construction of the database. The control of micro-movements represents an advance for the development of the manufacturing process, in addition to serving as a guide for any person involved in the manufacture of garments.
Keywords: micromovement; standard time; methods study; work measurement; layout